Window views in the built environment: preferences and behaviours - Batool, Ayesha (2021)
With 90% of our time spent indoors, and an estimated 75% of the world population living in cities by 2050, the challenge of designing habitats for people is of primary importance. From an evolutionary perspective, humans have only recently started to occupy buildings for the majority of their day. When inside buildings, windows are favoured by building occupants due to the view and connection to the outside that they afford, which positively affect their environmental satisfaction. Accordingly, based on the scientific literature, building guidelines have started to include specific criteria for designing window views – e.g., providing natural and long-distance views, containing various layers of information, etc. – to enhance appreciation and preference. However, there are still research gaps to be filled, particularly for designing window views in an urban context. Multi-layered natural views are improbable in dense urban settings. Also, existing studies are built upon subjective appraisals of different stimuli with results that are difficult to reproduce due to the inherent complexity and variability of the view out of a window. Even when the views hold specific environmental qualities, we still do not know how they would affect the observer’s perception and their resultant behaviour; that is how the occupants would engage with the window view. What features of views will encourage them to look out of the window? What will drive their gaze away from a task and towards the outside?